The Influence Of Transformational Leadership And Person-Organizational Fit On Innovative Work Behavior Through Knowledge Sharing Behavior In Formal Education Units - Adisti Hakim Wahyuningtias; Sukmo Hadi Nugroho (Universitas Trunodjoyo Madura, 2023)
This research purposes to explore the influence of transformational leadership and person-organizational fit on innovative work behavior through knowledge sharing behavior. This research is a development of previous research on employees in formal education units. The contribution of this research is expected to able providing new information at the theoretical level of human resource management science and become a reference and have positive managerial implications that can be applied in organizations. Referring to the results of previous research and empirical theory related to the learning process of human resource management, this research was conducted using a survey data collection method by spreading questionnaires online. The population in this study amounted to 28,406 teachers, with respondents selected using the purposive sampling method on teaching staff in the formal education unit at East Jakarta area of 105 teachers as research respondent data. In this study using factor analysis and modeling the Structural Equation Model (SEM) Lisrel. The invention of this study related obtained on transformational leadership do not have a significant positive relationship with innovative work behavior, but transformational leadership can have a positive impact on innovative work behavior through the mediation of knowledge sharing. The managerial implication of this research is that there is a need for leaders to engage with their subordinates in building communication and absorbing any new information as well as creating various kinds of innovations that can be applied and in line with organizational goals.